STUDI TENTANG MUTU TERJEMAHAN DAN IMPLIKASINYA TERHADAP PENGAJARAN MENERJEMAH - A Halim Majid (Center for Research and Community Service (LPPM) University of Abulyatama, 2017)
This study aims to know: (1) the accuracy of the translation of the Quran Surah Ali Imran published by Religious Affair, (2) the clarity of translation in terms of structure, diction, and spelling, and (3) the general readers’ responses to that surah. These objectives can be achieved through the qualitative and quantitative analysis by comparing the translation with the source passage through the utilization of the verse. Next, the researcher asked the general readers and expert readers on the clarity of Religious Affair‘s translation by comparing it with other translations. The analysis found that the translation is correct, but poorly understood by the reader because the sentence structure complicated, less precise choice of words, sentence length, and less careful in spelling. After this weakness improved and the general reader asked their responses, it was found that the improvement translation is easier to understand than Religious Affair’s translation. Therefore, it is suggested that the translation is aligned with some of the conclusions of this study.